The approach to sexual and reproductive health in immigrant women from a gender perspectiv - María Luisa Grande Gascón; Manuel Linares Abad; Carmen Álvarez Nieto; Guadalupe Pastor Moreno (Universidad de Alicante, 2012)
In recent years there has occurred a significant increase in the immigrant population resident in Spain. And if at the beginning of phenomenon of migration they emigrated alone men, nowadays a growing number of women are migrating, or as result of family re-unification, or as migration projects of themselves. This work aims to analyze, through a review of published literature, what are the factors that affect the sexual and reproductive health of immigrant women and what are the main barriers that they have on standardized access to the health services. In conclusion we can highlight that previous studies have shown that there are a number of factors that influence the sexual and reproductive health of female immigrants and that there is less use of health services for these, since there are multiple barriers that obstruct a normal integration in the public health system.